2020
DOI: 10.1038/s41598-020-70474-4
|View full text |Cite
|
Sign up to set email alerts
|

Personal identification with orthopantomography using simple convolutional neural networks: a preliminary study

Abstract: Forensic dental examination has played an important role in personal identification (PI). However, PI has essentially been based on traditional visual comparisons of ante-and postmortem dental records and radiographs, and there is no globally accepted PI method based on digital technology. Although many effective image recognition models have been developed, they have been underutilized in forensic odontology. The aim of this study was to verify the usefulness of PI with paired orthopantomographs obtained in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…The findings of this study are consistent with the accuracy levels reported by those authors, which ranged from 80% to 100%. 25 Similarly, Heinrich et al (2018) observed a high rate of successful identification (85%) in an automated comparison of AM and PM-simulated panoramic radiographs from a large database. 10 …”
Section: Discussionmentioning
confidence: 96%
“…The findings of this study are consistent with the accuracy levels reported by those authors, which ranged from 80% to 100%. 25 Similarly, Heinrich et al (2018) observed a high rate of successful identification (85%) in an automated comparison of AM and PM-simulated panoramic radiographs from a large database. 10 …”
Section: Discussionmentioning
confidence: 96%
“…Yoo et al reported on the application of artificial intelligence to predict the difficulty of surgery for third molar extraction [ 16 ]. The authors reported on an artificial intelligence-based analysis method for orthopantomography [ 17 ]. Artificial intelligence is increasingly being applied to the dental field [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…AI application in forensic odontology can also be used for automatic age estimation, sex determination, skeletal morphology identification and personal identification. [99][100][101][102][103][104][105] Deep CNN was used for age estimation through staging of third molar development corresponding to the Demirjian classification in panoramic radiographs. [100][101][102] The best stage allocation accuracy obtained was 61% in a fully manual segmentation process of the third molar.…”
Section: Screening Of Osteoporosismentioning
confidence: 99%
“…103 Patil et al (2020) also demonstrated the potential use of ANN for gender determination using mandibular morphometric parameters in panoramic radiographs. 104 Matsuda et al (2020) conducted a preliminary study to investigate the potential use of simple CNN architectures for personal identification by comparing 30 pairs of panoramic radiographs. 105 Despite the various promising results in the field of forensic odontology, further improvement of AI models is still needed.…”
Section: Screening Of Osteoporosismentioning
confidence: 99%